ASEAN Economic Community: Has Indonesia Done Its Homework? - Paramitha, Santi H. (2016)
ASEAN has entered a new era with the commencement of the ASEAN Economic Community (AEC). While Indonesian officials regard the AEC with optimism, there are concerns whether Indonesia can meet its obligations under the AEC.